Does the Inclusion of Truncation point in a Finite Mixture Model Improve Diameter Distribution Estimation of Degraded Stand?. (2nd January 2022) - Ogana, Friday Nwabueze
ABSTRACT: This study proposed an alternative approach that could be used to model irregular diameter distribution with fixed measurement threshold. Sixteen plots of 0.0625 ha size from a degraded teak ( Tectona grandis L. f.) stands were used as case study, in which only trees with diameter ≥ 10 cm were considered. Four methodologies were evaluated: method 1 used the Weibull distribution neglecting the truncation point and irregularities; method 2 utilized truncated Weibull distribution; method 3 used two components 2-parameter Weibull in a mixture model, and in method 4, two components truncated Weibull in a mixture model was used. The models were assessed with different indices including Kolmogorov-Smirnov and Anderson-Darling statistics. Relative rank sum of the models was analyzed with one-way analysis of variance. The result showed that model developed with method 4 had the smallest fit indices and relative rank which was significantly different from models obtained with other methods. It also had the smallest root mean square error (5.146 m 3 ha −1 ) and critical error (1.362 m 3 ha −1 ) for estimating stand volume in diameter classes. Thus, incorporating truncated Weibull in a finite mixture is the best strategy for modeling diameter distribution of degraded teak stands with fixed measurement threshold.